2016
DOI: 10.4236/fns.2016.78069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olive Oil and Grape Seed Oil on Lipid Profile and Blood Pressure in Patients with Hyperlipidemia: A Randomized Clinical Trial

Abstract: Background and Aims: Hyperlipidemia is one of clear risk factors of diabetes. Regarding its importance, this study was designed to compare the effects of olive oil and grape seed oil on serum lipids and blood pressure in patients with hyperlipidemia in 2015. Methods and Results: In this clinical trial, 60 patients with hyperlipidemia who met inclusion criteria were recruited. Subjects were randomly assigned 3 groups: 1) consume 20 ml/day refined olive oil; 2) consume 20 ml/day grape seed oil; 3) the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Therefore, grape seed oil has been reported as a suitable dietary supplement that may prevent or improve physiological disorders related to chronic diseases [ 35 , 109 ]. Notably, many questions related to bioavailability, dose response, and side effects in humans are still to be answered [ 125 , 126 ]. Nevertheless, we will address the main nutraceutical activities with the responsible oil components.…”
Section: Grape Seed Oil: a Novel Functional Foodmentioning
confidence: 99%
“…Therefore, grape seed oil has been reported as a suitable dietary supplement that may prevent or improve physiological disorders related to chronic diseases [ 35 , 109 ]. Notably, many questions related to bioavailability, dose response, and side effects in humans are still to be answered [ 125 , 126 ]. Nevertheless, we will address the main nutraceutical activities with the responsible oil components.…”
Section: Grape Seed Oil: a Novel Functional Foodmentioning
confidence: 99%
“…Tocotrienol in muscadine grape seed oil has been reported to play a significant role in reducing adipogenesis . Kaseb and Biregani reported that serum triglyceride concentrations in hyperlipidemic patients were significantly decreased after intervention with grape seed oil. Generally, the main clinical symptoms were dizziness, fatigue, and heart palpitations, and obesity patients are also apt to be tired.…”
Section: Discussionmentioning
confidence: 99%
“…Both seeds and fruit of the grape are commonly used as functional medicinal plant caused by anti dyslipidemic effect and antioxidant activities via free radical scavenging [25]. Red grape seed extract involves oligomeric proanthocynaidins and procyanidins as a major class of The pivotal biochemical action of grape seeds refleted by not only the rich content of polyphenols but also the replacement of saturated fatty acids by polyunsaturated fatty acids whereby all grape seeds has high percent of linoleic acid (60%-75%) and it is recognized for shifting lipid profile towards balance [24].…”
Section: -Hypolipidemic Action Of Grapes Vitis Viniferamentioning
confidence: 99%